Global Trends and Challenges for School Leaders: Keeping the Focus on Learning - Peter Earley (LED Edizioni Universitarie, 2016)
This paper gives consideration to global trends and recent developments in education systems, particularly as they relate to schools and school leaders operating in high stakes accountability cultures. The importance of leadership for organisation success is noted alongside a number of other key within-school factors such as teacher quality. Successful leaders are differentiated from high-performing leaders and the notion of «leadership for learning» is outlined. This leads to a discussion of the nature of learning - leading learning for what? - and the accountability pressures that make its enactment increasingly problematic whilst, in some cases, leading to undesirable practices. There is need for a cadre of proactive, reflective leadership professionals with social responsibilities. Education systems and schools need reflective professionals who are able to make judgements and act upon what is considered to be «educationally desirable». The challenges educational leaders face, both now and in the future, including keeping the focus on «learning» and seeing themselves as proactive reflexive leadership professionals, are also discussed.